2017
DOI: 10.1007/s11356-017-8598-0
|View full text |Cite
|
Sign up to set email alerts
|

Traffic represents the main source of pollution in small Mediterranean urban areas as seen by lichen functional groups

Abstract: The land-use type (residential, green areas, and traffic) within relatively small Mediterranean urban areas determines significant changes on lichen diversity, considering species richness and functional groups related to different ecological factors. Those areas with larger volume of traffic hold lower species diversity, in terms of species richness and lichen diversity value (LDV). Traffic areas also affect the composition of the lichen community, which is evidenced by sensitive species. The abundance of spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…S4), although our data does not allow to disentangle their effects as they co-occur. This is in accordance with what was observed in other studies (Llop et al, 2012;Llop et al, 2017), but was observed for the first time in multiple cities and with broad-scale air pollution. The air pollution model used (EMEP MSC-W) includes not only pollution sources and concentrations, but also climatic information.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…S4), although our data does not allow to disentangle their effects as they co-occur. This is in accordance with what was observed in other studies (Llop et al, 2012;Llop et al, 2017), but was observed for the first time in multiple cities and with broad-scale air pollution. The air pollution model used (EMEP MSC-W) includes not only pollution sources and concentrations, but also climatic information.…”
Section: Discussionsupporting
confidence: 93%
“…Air pollution has long been a high-intensity driver in urban areas due to the presence of local industrial and traffic pollutants within nearby cities (Babiy et al, 2003;Fenger, 1999), which translates to increased pollutant concentration or deposition (Krzyzanowski et al, 2014;Riga-Karandinos and Saitanis, 2005). Although the role of specific pollutants has been observed in several local-scale studies (Llop et al, 2017;Varela et al, 2018), our results suggest that on a broad scale, when multiple pollutants are superimposed, lichens respond to pollution overall rather than to specific pollutants. Because lichens absorb pollutants from wet and dry atmospheric deposition (Van Der Wat and Forbes, 2015), increased air pollution levels translate to an overall harmful effect on most lichen species, and result in consequent species loss, as reported by several authors in single-city studies (Gary, 2010;Koch et al, 2016;Munzi et al, 2007).…”
Section: Discussionmentioning
confidence: 60%
“…Despite these challenges, air quality in cities is of particular concern as many source apportionment studies have shown that traffic sources are a significant contributor to pollution [16,[34][35][36][37][38][39][40][41][42]. People living in close proximity to roadways are at risk of high exposures to air pollutants [43], and many urban populations of low SES groups typically live close to roadways [17,44,45].…”
Section: Introductionmentioning
confidence: 99%
“…However, cryptogams in the Mediterranean are not effective biomarkers for changes in water availability induced by climate change because they are affected by several stress factors in similar ways (Pirintsos et al 2011). Lichens have been efficiently used to identify local sources of atmospheric contamination in urban or highly contaminated industrial sites of the Mediterranean countries (Paoli et al 2006;Llop et al 2017;Ratier et al 2018). More rarely used in distant areas, lichen and mosses were successfully used as metal biomonitors in various environmental situations in France and over the last century.…”
Section: Biotic and Abiotic Indicators And Biomonitoring Of Air Qualitymentioning
confidence: 99%